Next-generation nanomedicines and nanosimilars: EU regulators' initiatives relating to the development and evaluation of nanomedicines. (May 2013) - Ehmann, Falk; Sakai-Kato, Kumiko; Duncan, Ruth; Pérez de la Ossa, Dolores Hernán; Pita, Ruben; Vidal, Jean-Marc; Kohli, Ashish; Tothfalusi, Laszlo; Sanh, Alan; Tinton, Sandrine; Robert, Jean-Louis; Silva Lima, Beatriz; et al.
Over the last three decades many first-generation nanomedicines have successfully entered routine clinical use and it is now important for medicines regulatory agencies to consider the mechanisms needed to ensure safe introduction of 'follow-on' nanomedicine products, 'nanosimilars'. Moreover, drug regulators need to ensure that 'next'-generation nanomedicines enter clinical development and consequently the market in a safe and timely way for the benefit of public health. Here we review recent European Medicines Agency activities that relate to the effective development and evaluation of nanomedicine products while keeping patient and consumer safety at the forefront.